65_RedRoses [videorecording (DVD)] - Mukerji, Nimisha; Lyall, Philip (OWN documentary club., 2012)
Provided is a personal and touching journey that takes an unflinching look into the lives of Eva Markvoort and her two online friends, who are all battling cystic fibrosis, a fatal genetic disease affecting the lungs and digestive system.